Analytical Pyrolysis - Kusch, Peter (IntechOpen, 2019)
Analytical pyrolysis deals with the structural identification and quantitation of pyrolysis products with the ultimate aim of establishing the identity of the original material and the mechanisms of its thermal decomposition. The pyrolytic process is carried out in a pyrolyzer interfaced with analytical instrumentation such as gas chromatography (GC), mass spectrometry (MS), gas chromatography coupled with mass spectrometry (GC/MS), or with Fourier-transform infrared spectroscopy (GC/FTIR). By measurement and identification of pyrolysis products, the molecular composition of the original sample can often be reconstructed.This book is the outcome of contributions by experts in the field of pyrolysis and includes applications of the analytical pyrolysis-GC/MS to characterize the structure of synthetic organic polymers and lignocellulosic materials as well as cellulosic pulps and isolated lignins, solid wood, waste particle board, and bio-oil. The thermal degradation of cellulose and biomass is examined by scanning electron micrography, FTIR spectroscopy, thermogravimetry (TG), differential thermal analysis, and TG/MS. The calorimetric determination of high heating values of different raw biomass, plastic waste, and biomass/plastic waste mixtures and their by-products resulting from pyrolysis is described.